i i 0 1 534b this formula makes sense when

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 3.4c) Substituting (5.3.4c) into (5.3.3a,b) yields Pk;1(t) = k ;1 X (;1)i ; i i=0 14 rifn;1 (5.3.5a) and, using (5.3.1), Ek;1(t) = (;1)k hk ; k y(k+1)( ): (5.3.5b) Replacing f (t y(t)) in (5.3.2) by Pk;1(t) + Ek;1(t) and transforming the integrals from t to using (5.3.4a) yields y(tn) = y(tn;1) + h Z 1X k ;1 0 i=0 ; (;1)i rifn;1 d i Let m = (;1)m Z ; 1 y(tn) = y(tn;1) + h i=0 i ri f n;1 + (;1)k hk+1 1 0 (;1)k hk ; k d: m 0 Then we have k;1 X +h Z Z 1 (5.3.6a) ; 0 y(k+1)( )d : k y(k+1)( )d : (5.3.6b) Dropping the error term yields the k-step Adams-Bashforth method yn = yn;1 + h The local error of this formula is dn = (;1)k hk+1 Z k;1 X i=0 1 ; k 0 i i r fn;1 : y(k+1)( )d : (5.3.7a) (5.3.7b) Comparing (5.3.7a) with the general multistep formula (5.1.2a), we see that 0 = 1, 1 = ;1, and 2 = 3 = : : : = k = 0 = 0. Thus, (5.3.7a) uses the one solution value yn;1 and the k function values fn;1, fn;2, : : : , fn;k to obtain the yn (cf. Figure 5.3.1). We'll call (5.3.7a) a k-step method since it uses solution and function values at the k points tn;1 , tn;2 , : : : , tn;k however, other terminology is also used 10]. From (5.3.7b) we see that the local error of (5.3.7a) is O(hk+1). Thus, the order of a k-step Adams-Bashforth method is k. The method (5.3.7) has only one function evaluation per step. This is contrasted to the minimum of k function evaluations that are needed for a k-stage Runge-Kutta method. 15 y y(t) f n-2 f n-k t n-k t n-2 yn-1 f n-1 t n-1 tn t Figure 5.3.1: Information needed for a k-step Adams-Bashforth method. The representation of (5.3.7a) in terms of backward di erences will be useful to us in some circumstances, but generally we prefer a formula written in terms of function values at preceding points. This can be done using q X jq qf r n;1 = (;1) j fn;1;j : (5.3.8a) j =0 Then, using (5.3.7a) yn = yn;1 + h k;1 i XX i=0 i j =0 (;1)j if j n;1;j : (5.3.8b) By rearranging the order of the computation (5.3.8b) can be written in the form (Problem 1) yn = yn;1 + h where j = k;1 X i=j ;1 i k...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online